REVIEW PEMANFAATAN SAMPAH PLASTIK UNTUK ENERGI DAN BAHAN KONSTRUKSI - Qomaruddin, Mochammad; Tristan, Alfian; Faqih, Nasyiin; Roehman, Fatchur; Mushthofa, Mushthofa (Universitas PGRI Semarang, 2024)
The problem of plastic waste has become a global concern due to its negative impact on the environment. Plastic, as a non-biodegradable material, results in significant pollution of soil and water. As plastic production increases, efforts to find innovative solutions in reducing environmental impact are important. This article discusses the use of plastic waste as an alternative energy source and construction material. Using a liter-tour review method from various sources that explores the potential of plastics to be converted into energy as well as their use in building materials and as aggregates in concrete. The results of the analysis show that the use of plastic waste can not only reduce pollution, but also provide economic and social benefits, especially as fuel oil and building materials such as paving plastic, plastic aggregate, asphalt plastic mixture.Â